Rumus dan data dalam analisis statistika : untuk penelitian (adminitrasi pendidikan-bisnis-pemerintahan-sosial-kebijakan-ekonomi-hukum-manajemen-kesehatan) - Riduwan (Alfabeta, 2007)
viii, 304 p. : ill.; 24 cm